Case Report: Guillain-Barré Syndrome as Primary Presentation of Systemic Lupus Erythematosus (SLE-GBS) in a Teenage Girl - Elham Beshir; Ernestina Belt; Nidheesh Chencheri; Aqdas Saqib; Marco Pallavidino; Marco Pallavidino; Ulrich Terheggen; Abdalla Abdalla; Leal Herlitz; Elsadeg Sharif; Martin Bitzan; Martin Bitzan (Frontiers in Pediatrics, 2022)
Peripheral nervous system involvement accounts for fewer than 10% of SLE cases with neuropsychiatric manifestations. Guillain-Barré syndrome (GBS) as the presenting, major manifestation of pediatric SLE is extremely rare, and the best treatment approach is unknown. A 14-year-old, previously healthy female teenager developed classic features of GBS with ascending bilateral muscle weakness leading to respiratory insufficiency, associated with protein-cell dissociation in cerebro-spinal fluid, nerve root enhancement by MRI and reduction in compound muscle action potential amplitude. SLE was diagnosed serologically and histologically (lupus nephritis WHO class II). Despite immediate treatment with intravenous immunoglobulin (IVIg), methylprednisolone pulses and subsequently, rituximab, the patient required prolonged mechanical ventilation. She achieved full recovery following 14 PLEX treatments and two more rituximab infusions. Anti-dsDNA, C3, C4 and urinalysis normalized while anti-Smith and Sjögren antibodies persisted 15 months after disease onset, with no other lupus manifestations. Review of the literature revealed two pediatric cases of GBS at the onset of SLE and a third case with GBS 6 years after the diagnosis of SLE. Conventional GBS therapy may not be adequate to treat SLE-GBS. SLE should be included in the differential diagnosis of GBS. Importantly, treatment experiences and outcomes of such cases need be reported to inform future treatment recommendations.